Sales ethics : how to sell effectively while doing the right thing - Alessandri, Alice; Aleo, Alberto (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2015)
Do ethics pay? In an attempt to answer this question, the authors analyze the economic theories that might rehabilitate ethics in the world of sales and turn them into an effective tool for conducting negotiations. This book proposes a bottom-up approach that starts from an analysis of sales activities to build a business style that, if adopted by an entire organization, can make a difference, thus enhancing the company's success. Italian culture provides a backdrop to the book; the authors reinterpret the particular nature of the country's economic and social fabric and integrate this in an approach to business that can create authentic relationships, shared prosperity, and quality of life across other cultures. Sale Ethics stimulates the development of a self-entrepreneurial mindset that is useful in any field, and provides a simple and effective method of capitalizing on your own talents while respecting others and at the same time garnering the rewards of ethical behavior.
1. Why read a book on sales ethics? -- 2. The key concepts in sales ethics -- 3. The economic theories underlying sales ethics -- 4. Preparing for negotiations -- 5. The phases of sales ethics -- Conclusions: the second step -- FAQ: Our answers to your questions -- References -- Bibliography -- Index.
Includes bibliographical references (pages 205-208) and index.
Title from PDF title page (viewed on May 22, 2015).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2016. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Selling -- Moral and ethical aspects; Business ethics; customer relationship; effectiveness; negotiation technique; reciprocity; Sales Ethics; sales strategy; trust; value; well-being; Electronic books